Investigating The Impact of Sensory Experience on Budget Hotel Rooms to Maximize Guests Satisfaction - Reiza Miftah Wirakusuma; Anak Agung Anom Samudra; Ni Kadek Sumartini (Institut Pariwisata dan Bisnis Internasional, 2021)
This study aims to investigate the sensory experience from guests who have stayed at a budget hotel in Bandung, West Java Province. Although only offers low prices, simple facilities, and less spacious room, yet a budget hotel has been able to maximize comfort and satisfaction for their guests. Subsequently, the number of budget hotels increase significantly in the past few decades and create different themes for hospitality industry. These themes create unique experience and they are felt by five senses of guests during their visits. The experience is divided into visual, tactile, gustatory, auditory, and olfactory. The method used in this research is a qualitative descriptive analysis from 145 questionnaires which were collected on the field. The results showed that the sensory experience had a dominant impact on guest satisfaction in staying at a budget hotel, especially in tactile and visual.